Strategi Komunikasi Islam Komunitas Muslim Upgrade Dalam Memotivasi Pentingnya Pendidikan di Kalangan Remaja Desa Denai Sarang Burung Kecamatan Pantai Labu - Nurhaida Nadila; Elfi Yanti Ritonga (EduInovasi: Journal of Basic Educational Studies, 2023)
This research is about the Islamic communication strategy played by the Upgrade Muslim Community which aims to motivate the importance of education among adolescents in Denai Nest Bird Village, Pantai Labu District. This study uses field observation research and interviews with qualitative methods. The fundamental reason for raising this phenomenon by researchers is because the Upgrade Muslim Community is able to influence the people in the village by using the Qur'an and hadith as a guide to convey messages that can motivate the community. Qaulan sadidan and qaulan balighan are the principles of Islamic communication used. To create a quality, educated generation is the right effort for this, therefore it is very important for teenagers to prioritize education. The upgraded Muslim community conducts outreach, seminars and makes banners to convey things that can change people's mindsets. Apart from that, social media is also used as a means of disseminating information and means of communication in realizing the strategies that have been designed. There are several obstacles that occur in carrying out these activities, but these obstacles can be resolved appropriately by the community itself. The Islamic communication strategy used is an effective strategy to achieve the stated goals. Keyword : Strategy, Islamic Communication, Education